1981
DOI: 10.3382/ps.0602045
|View full text |Cite
|
Sign up to set email alerts
|

Specific Gravity, Carcass Fat, Abdominal Fat, and Yield Data in Broiler Chickens

Abstract: Specific gravity of the eviscerated broiler carcasses of 100 males and 100 females (59 days old) in one experiment and 50 males and 50 females (55 days old) in a second experiment was determined. Carcass fat was measured as ether extractable solids of the ground carcass. Yield data on starvation loss, percentage of blood and feathers, viscera, intestines, percentage carcass moisture and abdominal fat, and percentage protein and ash in the carcass were provided in both experiments.The correlation coefficients b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The correlations of .72 and .74 for percentage carcass fat with abdominal and sartorial fat weights, respectively, were similar, highly significant, and consistent with those reported in chickens by Spencer et al (1978), Summers and Leeson (1979), Becker et al (1981), and Burgener et al (1981). Conversely, Deaton et al (1973), Cunningham and Morrison (1976), and Griffiths et al (1977) noted that the weight of the abdominal fat depot did not necessarily reflect the percentage of carcass fat in chickens.…”
Section: Resultssupporting
confidence: 89%
“…The correlations of .72 and .74 for percentage carcass fat with abdominal and sartorial fat weights, respectively, were similar, highly significant, and consistent with those reported in chickens by Spencer et al (1978), Summers and Leeson (1979), Becker et al (1981), and Burgener et al (1981). Conversely, Deaton et al (1973), Cunningham and Morrison (1976), and Griffiths et al (1977) noted that the weight of the abdominal fat depot did not necessarily reflect the percentage of carcass fat in chickens.…”
Section: Resultssupporting
confidence: 89%
“…This is true for house sparrow ( Passer domesticus ) (SG = 1.05), domestic chicken ( Gallus gallus ) (SG = 1.044), and quail ( Coturnix japonica ) (SG >1.053) (Tserveni & Yannakopoulos, 1988; table 3 in Hamershock et al, 1993). SGs in the region of 1.05 have been also found in broiler and Bronze turkey eviscerated carcasses (Becker, Spencer, Mirosh, & Verstrate, 1981; Essary, Dawson, Wisman, & Holmes, 1965; Moran Jr, Summers, & Orr, 1968; Moreng, Whittet, & Enos, 1963). Wilson et al (1992) observed that the SG without air in ducks (Anatidae and Alcidae), divers (Gaviidae), penguins (Spheniscidae), and cormorants (Phalacrocoracidae) are generally very close to 1.0 or higher.…”
Section: Methodological Considerationsmentioning
confidence: 94%
“…A rather low correlation between specific gravity and carcass grade of r = .165 was determined by Moran et al (1968). In more recent works, Becker et al (1981) reported specific gravity to fat correlations of from -.31 to -.36 and -.58 to -.69 for male and female broilers, respectively, while Fortin and Chambers (1981) reported a linear correlation (R 2 ) of .36 for predicting total fat from specific gravity.…”
Section: Introductionmentioning
confidence: 95%
“…Becker et al (1979Becker et al ( , 1981 reported correlations ranging from .51 to .76 between abdominal fat pad (as a percent of live weight) and total carcass fat. Becker et al (1979) reported a model correlation (R 2 ) of .82 between fat pad weight and weight of fat in the carcass.…”
Section: Introductionmentioning
confidence: 96%